Miocene Antarctic Ice Sheet area adapts significantly faster than volume to CO2-induced climate change - L. B. Stap; C. J. Berends; R. S. W. van de Wal; R. S. W. van de Wal (Climate of the Past, 2024)
The strongly varying benthic δ18O levels of the early and mid-Miocene (23 to 14 Myr ago) are primarily caused by a combination of changes in Antarctic Ice Sheet (AIS) volume and deep-ocean temperatures. These factors are coupled since AIS changes affect deep-ocean temperatures. It has recently been argued that this is due to changes in ice sheet area rather than volume because area changes affect the surface albedo. This finding would be important when the transient AIS grows relatively faster in extent than in thickness, which we test here. We analyse simulations of Miocene AIS variability carried out using the three-dimensional ice sheet model IMAU-ICE forced by warm (high CO2, no ice) and cold (low CO2, large East AIS) climate snapshots. These simulations comprise equilibrium and idealized quasi-orbital transient runs with strongly varying CO2 levels (280 to 840 ppm). Our simulations show a limited direct effect of East AIS changes on Miocene orbital-timescale benthic δ18O variability because of the slow build-up of volume. However, we find that relative to the equilibrium ice sheet size, the AIS area adapts significantly faster and more strongly than volume to the applied forcing variability. Consequently, during certain intervals the ice sheet is receding at the margins, while ice is still building up in the interior. That means the AIS does not adapt to a changing equilibrium size at the same rate or with the same sign everywhere. Our results indicate that the Miocene Antarctic Ice Sheet affects deep-ocean temperatures more than its volume suggests.